A eficácia e a execução (enforcement) da sentença arbitral nacional e estrangeira: a(im)possibilidade de reexame do mérito da decisão arbitral pelo Poder Judiciário nacional - Oliveira, Caio Marra Moreira Rodrigues de (2022)
This academic work addresses the effectiveness and effects of the arbitration award in Brazil, whether rendered in the national territory or in a foreign country, considering especially the enforcement of the arbitration award in case of non spontaneous compliance with the obligation constituted by the award resulting from the arbitration proceeding.In this scenario, starting from a priori analysis of the effectiveness of the arbitration award and the res judicata, we seek to analyze the (im)possibility of reexamination of the merits of the arbitration award by the Brazilian Judiciary.After all, in the field of positive law, it is clear that there are material limitations regarding the judgment of requests for homologation, enforcement and execution of arbitration awards, which are mainly embodied in articles 32 and 37 to 39 of Law No. 9307/1996 ("Arbitration Law"), as well as in the Brazilian Civil Procedure Code.By the sole analysis of the legal statement, it would be theoretically impossible for the Judiciary to rediscuss the merits of the arbitration award. This academic work, however, seeks to demonstrate that the provisions of the Arbitration Law are not always observed in their literalness, so that the Brazilian case law sometimes admits the re-examination of the merits of the arbitration award by the national Judiciary